Consumer Decisions in Purchasing Coffee Drinks at Humble Salatiga Shop During the Covid-19 Pandemic - Arinta Rambu Juni Rana; Lasmono Tri Sunaryanto (Journal of Social Research, 2023)
This study aims to: Find out consumers' decision-making in buying coffee drinks at humble shops. This type of research is descriptive qualitative. Participants were selected based on 3 criteria, namely consumers who bought coffee drinks for a period of 2-3 times or even more in a month, loyally recommended to their friends or family, and would remain loyal to shopping at humble shops. Data analysis techniques in this study include (1) data reduction (2) data presentation (3) verification and (4) drawing conclusions. The results showed that: 1) The Covid-19 pandemic is not a problem for consumers at Kedai Humble, and the presence and absence of the Covid-19 pandemic is not a threat to loyal consumers at Kedai Humble. Consumers will continue to shop offline at Humble stores while still complying with health protocols that have been set by the government 2) stages of consumer purchasing decision-making, namely problem recognition, information search, alternative evaluation and purchase decisions 3) Factors that influence consumer decisions, namely relatively affordable prices and local environmental conditions that make them comfortable.